Association between “Life's Essential 8” cardiovascular health and apparent treatment-resistant hypertension among US adults from the NHANES, 2005 to 2018 - Xu, Zhong-jiao; Shen, Ru-ming; Hu, Wu-ming; Shen, Jia-yi; Wu, Xiao-yan; Lv, Ling-chun (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe association between healthy lifestyle and American Heart Association (AHA) Life's Essential 8 (LE8) score and apparent treatment-resistant hypertension(aTRH)remains uncertain. We aimed to explore the association between healthy lifestyle and higher LE8 score and apparent treatment-resistant hypertension in the general population.MethodsUsing NHANES data from 2005 to 2018, we included and analyzed information on 7,474 participants eligible for this study. The association between LE8 and aTRH was explored using logistic regression models, and the association between LE8 and antihypertension drugs uncontrolled hypertension was further explored using logistic regression models.ResultsParticipants with higher LE8 scores tended to be non-Hispanic white and married or living with a partner; have low income and higher education; and be without Chronic kidney disease (CKD)(all p-values <0.001). Compared to subjects with low CVH, participants with moderate and high CVH exhibited lower risks of 47% and 76%, respectively. After adjusting for covariates, there was no evidence of a nonlinear association between LE8 and aTRH (p for nonlinearity = 0.456). Physical activity (PA), body mass index (BMI), and blood glucose were associated with aTRH (all p-values < 0.05), while diet, nicotine exposure, sleep, and blood lipids were not significantly associated with aTRH. Compared to the low LE8 group, the ORs for the high LE8 group were 0.46 (95% CI, 0.28 to 0.76) and 0.07 (95% CI, 0.02 to 0.20) for uncontrolled hypertension with 1–2 and 3–4 antihypertensive drugs, respectively. In the sensitivity analysis, subgroup analyses were performed on all covariates, and the results remained stable.ConclusionIn our study, we found a significant association between higher LE8 scores and a lower risk of aTRH. Our findings suggest that implementing various healthy lifestyle practices and managing known cardiovascular risk factors could be a feasible comprehensive preventive approach to aTRH.